Detection of novel germline mutations in six breast cancer predisposition genes by targeted next‐generation sequencing. Issue 10 (2nd August 2018) - Dong, Li; Wu, Nan; Wang, Shaojing; Cheng, Yanan; Han, Lei; Zhao, Jing; Long, Xinxin; Mu, Kun; Li, Menghui; Wei, Lijuan; Wang, Wanheng; Zhang, Weijia; et al.
Abstract: In this study, a customized amplicon‐based target sequencing panel was designed to enrich the whole exon regions of six genes associated with the risk of breast cancer. Targeted next‐generation sequencing (NGS) was performed for 146 breast cancer patients (BC), 71 healthy women with a family history of breast cancer (high risk), and 55 healthy women without a family history of cancer (control). Sixteen possible disease‐causing mutations on four genes were identified in 20 samples. The percentages of possible disease‐causing mutation carriers in the BC group (8.9%) and in the high‐risk group (8.5%) were higher than that in the control group (1.8%). The BRCA1 possible disease‐causing mutation group had a higher prevalence in family history and triple‐negative breast cancer, while the BRCA2 possible disease‐causing mutation group was younger and more likely to develop axillary lymph node metastasis ( P  < 0.05). Among the 146 patients, 47 with a family history of breast cancer were also sequenced with another 14 moderate‐risk genes. Three additional possible disease‐causing mutations were found on PALB2, CHEK2, and PMS2 genes, respectively. The results demonstrate that the six‐gene targeted NGS panel may provide an approach to assess the genetic risk of breast cancer and predict the clinical prognosis of breast cancer patients. Abstract : A targeted next‐generation sequencing (NGS) panel was designed to enrich the whole exons of six breast cancer predisposition genes. After sequencing was performed, sixteen possible disease‐causing mutations were identified in 20 samples. The percentages of possible disease‐causing mutation carriers in the breast cancer group (8.9%, 13/146) and in the high‐risk group (8.5%, 6/71) were higher than that in the control group (1.8%, 1/55). This six‐gene targeted NGS panel may provide an approach to assess the genetic risk of breast cancer.